The Role of Digital Literacy in Teaching the Islamic Education - Shofiyah, Luthfi Nurul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to describe efforts to determine the role of digital literacy in learning Islamic Religious Education in MAN 2 Surakarta. This research method uses a qualitative approach, which is sourced from primary data. The primary data source was obtained from an interview with one of the teachers of PAI MAN 2 Surakarta subjects related to digital literacy in the learning process of Islamic Religious Education at MAN 2 Surakarta. The results of this interview show that MAN 2surakarta students utilize CBT E-Learning y through which can be accessed via YouTube, Digital literacy as a learning tool that invites students to explore and develop learning materials using website-based learning media. From the results of interviews regarding digital competency frameworks. The framework consists of a set of skills that teachers and students have when using and utilizing digital-based learning tools.